Prevalence of radiographic osteoarthritis and structural abnormalities of the hip in patients with contralateral hip fractures - Pongtep Na Nakorn (2018)
© 2016, Medical Association of Thailand. All rights reserved. Background: The prevalence of osteoarthritis (OA) of the hip varies considerably among different races and ethnicities. Some bony abnormalities associated with the development of hip OA. Objective: To determine the prevalence of radiographic OA and structural abnormalities of the hip in patients with contralateral hip fractures. Material and Method: Pelvic AP radiographs of patients more than 60 years of age who had contralateral hip fractures were reviewed. Radiographic diagnosis of hip OA was determined by minimum joint space width ≤2 mm. Kellgren-Lawrence classification was also used for evaluation. Structural abnormalities of the acetabulum and proximal femur regarding femoroacetabular impingement were also assessed. Results: Plain radiographs of 152 patients with an average age of 77.4 years were included. One hundred and thirteen patients (74.3%) were female. Prevalence of radiographic OA of the hip (minimum joint space width ≤2 mm) was 9.9%. In addition, 9.2% of hips were Kellgren-Lawrence grade 2 or higher. Pistol grip deformity was found in 6 patients and all were male. Five patients (3.3%) had cross-over sign. No protrusio acetabuli was detected. Coxaprofunda was identified in 72 patients (47.4%). Average center-edgeangle was 37.1±6.2 degrees in hips with coxaprofunda, and 35.9±5.3 degrees in hips without coxaprofunda (p = 0.180). Conclusion: Prevalence of radiographic OA of the hip in patients with contralateral hip fractures was 9.9%. Coxaprofunda was a common radiographic finding.